Kekerabatan Bahasa Minangkabau di Nagari Mungo Kecamatan Luak Kabupaten Lima Puluh Kota dan Bahasa Melayu Riau di Desa Buantan Besar Kecamatan Siak Sri Indrapura Kabupaten Siak - Ana A'laikum; Ermanto (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2023)
This research aims to (1) determine the percentage level of kinship between the two languages studied, (2) determine the length of time of separation between the two languages studied, and (3) determine the sound correspondence between the languages studied. This type of research is quantitative and qualitative research with the field of comparative historical linguistics. The research object of this study is the Minangkabau language spoken by people in Nagari Mungo, Luak District, Lima Puluh Kota Regency and Riau Malay language spoken by people in Buantan Besar Village, Siak Sri Indrapura District, Siak Regency. The data of this study are oral and written which are guided by the Morris Swadesh vocabulary list and the cultural vocabulary list of the two languages. Based on calculations and existing research data, it was found that the cognate vocabulary between Minangkabau language in Nagari Mungo, Luak Subdistrict, Lima Puluh Kota Regency and Riau Malay language in Buantan Besar Village, Siak Sri Indrapura Subdistrict, Siak Regency was 371 cognate words and 129 non-cognate words. Therefore, the percentage level of kinship between the two languages is 75.5%. Furthermore, based on the calculation of the glottochronology method, it was found that the separation time between the two languages was 693 years later. Based on the five hundred vocabularies encountered, there are sound correspondences consisting of 175 form similarity vocabularies, 101 sound/phoneme replacement vocabularies, 82 sound/phoneme subtraction vocabularies, and 13 sound/phoneme additions with sound correspondences.